Heavy metal and metalloid pollution: A systematic review of health implications for pregnant women, children, and geriatrics in the East African region - Godswill J. Udom; Brian Turyahabwe; Ayodeji Aturamu; Omoirri M. Aziakpono; Richard D. Agbana; Omole G. Joseph; Nita-wills G. Udom; Nuru Mugide; Omali P. Odey; Haron Olot; Orish E. Orisakwe (Environmental Advances)
Heavy metal(loid) contamination in East Africa is a critical public health challenge, particularly affecting vulnerable populations such as pregnant women, children, and the elderly. Despite increasing industrialisation and mining activities in the region, there is a lack of comprehensive analysis addressing the exposure pathways and associated health implications of these toxicants. The study aims to bridge this gap by examining the sources, exposure routes, and health impacts of heavy metal(loid)s in East African communities. The study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The included studies were assessed for quality using the Critical Appraisal Skills Programme checklists and analysed using the narrative synthesis method. A risk-of-bias assessment was conducted using the Risk-of-bias VISualization (robvis) tool. The search generated 1025 papers, of which 31 met the inclusion criteria. Findings reveal significant health consequences categorised into maternal complications, developmental effects, and systemic disorders. Maternal exposure to lead, mercury, and cadmium correlates with gestational hypertension, preterm births, and developmental toxicity in offspring. In children, neurodevelopmental delays, reduced cognitive function, and growth impairments are prominent outcomes. The elderly experience exacerbated risks of cardiovascular diseases, renal dysfunction, and neurodegenerative disorders (for example, Parkinsonism and Alzheimer's disease) due to bioaccumulated metals. To mitigate these exposure-associated risks, regional collaborations and public health interventions (e.g., eco-friendly manufacturing processes, effective environmental monitoring policies, and improved waste management systems) must be implemented. To this end, this study provides a foundation for evidence-based strategies to protect vulnerable populations and promote sustainable development in East Africa.